1993
DOI: 10.1002/1097-0142(19930915)72:6<1819::aid-cncr2820720605>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Dna flow cytometry of stomach cancer. Prospective correlation with clinicopathologic findings

Abstract: Background. DNA ploidy and S-phase fraction measured by DNA flow cytometry were shown to correlate with several clinicopathologic characteristics in several types of tumors.Methods. DNA flow cytometry was performed on 329 samples (164 normal mucosa, 165 tumors) obtained from 165 patients (112 men) with stomach cancer, and the findings were correlated with various clinicopathologic characteristics of the patients in a prospective manner.Results. Seventy-nine of 165 samples (48%) from the tumors gave an aneuploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
10
2
Order By: Relevance
“…The results of the Trans-Tasman Radiation Oncology Group study (TROG) 99.02 also showed that T1-2 anal carcinomas require elective inguinal radiation treatment 32. Our study found that the 5-year actuarial rate of inguinal recurrence was 17.0%, which is consistent with previous reports 23. Inguinal lymph node treatment is necessary for patients with anal carcinoma.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the Trans-Tasman Radiation Oncology Group study (TROG) 99.02 also showed that T1-2 anal carcinomas require elective inguinal radiation treatment 32. Our study found that the 5-year actuarial rate of inguinal recurrence was 17.0%, which is consistent with previous reports 23. Inguinal lymph node treatment is necessary for patients with anal carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…The patients with positive inguinal lymph nodes had a poorer survival than those with negative inguinal lymph nodes (19.1% vs. 46.9%, respectively, p= 0.007). In previous studies, the risk for subclinical disease in the inguinal lymph nodes ranged from 18% to 28% 23. Therefore, we inferred that the inguinal lymph node is a high-risk region requiring significant clinical attention.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…DNA ploidy and SPF were determined by DNA flow cytometry as previously described (Lee et al, 1993). Samples were frozen rapidly in polypropylene screw-cap tubes, and stored in a freezer at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Well-differentiated and moderately differentiated carcinomas display aneuploid patterns more frequently than poorly differentiated tumors [4, [42][43][44][45], though some reports have not agreed with that conclusion [36,46].…”
Section: Gastric Cancer and Dna Aneuploidymentioning
confidence: 99%